2012
DOI: 10.1080/13803395.2011.630648
|View full text |Cite
|
Sign up to set email alerts
|

Differential response patterns on the Personality Assessment Inventory (PAI) in compensation-seeking and non-compensation-seeking mild traumatic brain injury patients

Abstract: There is relatively little research on the Personality Assessment Inventory (PAI) with mild traumatic brain injury (MTBI) populations. There is also little research on how compensation-seeking status affects personality assessment results in MTBI patients. The current study examined the PAI scales and subscales in two MTBI groups, one composed of compensation-seeking MTBI patients and the other consisting of non-compensation-seeking MTBI patients. Results indicated significant differences on several scales and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 34 publications
3
12
0
Order By: Relevance
“…Their findings are consistent with previous research in which high scores on NIM have been associated with poor effort on PVTs or compensation-seeking populations (see Lange, Pancholi, Bhagwat, Anderson-Barnes, & French, 2012). For instance, higher NIM scores were observed for compensation-seeking patients with mild TBIs than for patients who were not compensation seeking but also had mild TBIs (Whiteside, Galbreath, Brown, & Turnbull, 2012). Furthermore, in an examination of the PAI validity scales in relation to cognitive effort as measured by the Test of Memory Malingering (TOMM; Tombaugh, 1996), the INF and NIM scales were found to be significantly related to the TOMM (Whiteside, Dunbar-Mayer, & Waters, 2009).…”
Section: Pai In Psychological Injury and Related Evaluationssupporting
confidence: 92%
“…Their findings are consistent with previous research in which high scores on NIM have been associated with poor effort on PVTs or compensation-seeking populations (see Lange, Pancholi, Bhagwat, Anderson-Barnes, & French, 2012). For instance, higher NIM scores were observed for compensation-seeking patients with mild TBIs than for patients who were not compensation seeking but also had mild TBIs (Whiteside, Galbreath, Brown, & Turnbull, 2012). Furthermore, in an examination of the PAI validity scales in relation to cognitive effort as measured by the Test of Memory Malingering (TOMM; Tombaugh, 1996), the INF and NIM scales were found to be significantly related to the TOMM (Whiteside, Dunbar-Mayer, & Waters, 2009).…”
Section: Pai In Psychological Injury and Related Evaluationssupporting
confidence: 92%
“…Elevations on PVTs and SVTs are related to compensationseeking and higher levels of psychiatric comorbidities, such as PTSD and depression, but not demographic variables or injury characteristics in those with a history of mTBI [27,29,[31][32][33][34]. The benefits of using an embedded SVT such as the Validity-10 are twofold.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have examined the relationship between PAI scales and performance on PVTs. Researchers have found reliable elevations across the Somatic Complaints scale (SOM) in the context of lower PVT scores (Lange, Pancholi, Bhagwat, Anderson-Barnes, & French, 2012;Sumanti, Boone, Savodnik, & Gorsuch, 2006;Whiteside, et al, 2010;Whiteside, Galbreath, Brown, & Turnbull, 2012), and additional evidence in external incentive contexts supports these findings (Wagner, Wymer, Toppings, & Pritchard, 2005).…”
Section: Pai and Pvt Researchmentioning
confidence: 95%
“…Research on the PAI validity scales have consistently found elevations on the Negative Impression Management (NIM) scale in the context of PVT failure and symptom exaggeration (Gaasedelen et al, 2017;Keiski et al, 2015;Lange et al, 2012;Whiteside et al, 2009;Whiteside et al, 2012). Keiski et al (2015) performed an in-depth simulation study examining the differences in PAI validity scales between two groups simulating TBI: one group that simulated global symptoms (i.e., somatic, psychiatric, and cognitive symptoms), and another 'defensive' group that only simulated cognitive symptoms.…”
Section: Pai and Pvt Researchmentioning
confidence: 99%
See 1 more Smart Citation